2007
DOI: 10.1158/0008-5472.can-06-3870
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Growth 4 Suppresses Cell Spreading and Cell Migration by Interacting with a Novel Binding Partner, Liprin α1

Abstract: Inhibitor of growth 4 (ING4) is a candidate tumor suppressor that plays a major role in gene regulation, cell cycle control, apoptosis, and angiogenesis. ING4 expression is downregulated in glioblastoma cells and head and neck squamous cell carcinoma. Here, we identified liprin A1/PPFIA1, a cytoplasmic protein necessary for focal adhesion formation and axon guidance, as a novel interacting protein with ING4. ING4 and liprin A1 colocalized at lamellipodia in the vicinity of vinculin. Overexpressed ING4 suppress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 25 publications
7
106
0
Order By: Relevance
“…Liprin-a proteins may interact with different ligands, including liprin-b, the tyrosine phosphatase receptor LAR, kinesin motor proteins, the ArfGAP GIT1 and the adaptor proteins ERC and CASK (see de Curtis, 2011 for a review). Liprin-a1 is required for the assembly of neuronal synapses (Spangler and Hoogenraad, 2007) and is implicated in the regulation of non-neuronal cell migration (Shen et al, 2007). We have recently shown that liprin-a1 is an essential regulator of cell spreading on extracellular matrix (ECM) (Asperti et al, 2009(Asperti et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Liprin-a proteins may interact with different ligands, including liprin-b, the tyrosine phosphatase receptor LAR, kinesin motor proteins, the ArfGAP GIT1 and the adaptor proteins ERC and CASK (see de Curtis, 2011 for a review). Liprin-a1 is required for the assembly of neuronal synapses (Spangler and Hoogenraad, 2007) and is implicated in the regulation of non-neuronal cell migration (Shen et al, 2007). We have recently shown that liprin-a1 is an essential regulator of cell spreading on extracellular matrix (ECM) (Asperti et al, 2009(Asperti et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…5,[9][10][11][12][13][14] ING4 can also enhance chemosensitivity to DNA-damage agents such as doxorubicin and etoposide in HepG2 hepatocarcinoma cells. 10 Furthermore, ING4 can exhibit remarkable inhibitory effect on tumor cell spreading, migration and invasion via colocalization and interaction with liprin a1 at lamellipodia 15 and downregulation of matrix metalloproteinase-2 and matrix metalloproteinase-9. 11,16 In addition, ING4 can suppress the loss of contact inhibition elicited by myelocytomatosis viral related oncogene, neuroblastoma derived or myelocytomatosis viral oncogene homolog.…”
Section: Introductionmentioning
confidence: 99%
“…The association between ING4 and H3K4me3 augments HBO1 acetylation activity on H3 tails and drives H3 acetylation at ING4 target promoters [12]. ING4 also co-localizes with Liprina1 in the lamellipodia of cells and inhibits cell spreading and migration, suggesting that ING4 has additional functions in the cytoplasm [3]. All these studies indicate that ING4 performs its biological functions by associating with other proteins.…”
Section: Discussionmentioning
confidence: 90%
“…ING4binds to AUF1 p40 by pull down (View interaction) ING4physically interacts with AUF1 by anti tag coimmunoprecipitation (View Interaction: 1, 2) ING4binds to AUF1 p37 by pull down (View Interaction: 1, 2) ING4 binds to AUF1 p42 by pull down (View interaction) ING4binds to AUF1 p45 by pull down (View interaction) ING4physically interacts with AUF1 by anti bait coimmunoprecipitation (View Interaction: 1,2,3,4,5,6) ING4binds to AUF1 by pull down (View interaction)…”
Section: Structured Summary Of Protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation